Stimulants augmentation with an antidepressant for the treatment of the major depressive disorder (MDD) - F. Marashdeh, Dr. Muath; R. Haddad, Dr. Eva; A. Obaisat, Dr. Maxim; M. Al-Alwan, Dr. Malik (International Journal of Scientific Research and Management (IJSRM), 2019)
The use of antidepressants and sedative drugs is the best treatment proved for major depressive disorder and in some cases the electrical convulsion therapy. The use of stimulants off-label in clinical practice an increasing concern as there is no research evidence to support their effectiveness.